Social and clinical aspects of oncological patients of a chemotherapy service - Marilia Aparecida Carvalho Leite; Denismar Alves Nogueira; Fábio de Souza Terra (Rev Rene)
Objective: to identify the social and clinical aspects of oncological patients undergoing chemotherapy in a health clinic. Methods: it is an epidemiological cross-sectional research. A semi-structured script was used, applied to 156 patients. Results: there was a larger proportion of men (51.9%); age range between 51 to 60 years (30.8%); married (30.8%); incomplete and complete grade school (61.6%); retired/pensioners (57.0%); catholic (80.8%); nonsmokers (80.1%); non alcoholic beverages, users (60.9%) and sedentary (75.6%). The larger proportion of cancer was breast cancer (19.9%) and 37.2% in stages 3 and 4. The diagnosis and the treatment occurred in a period equal or inferior to six months. Most of the patients did not show chronical diseases (51.9%) and without the continuous use of medicine (51.9%). Conclusion: the knowledge of the social and clinical aspects of the patients under chemotherapy allows the nurse the planning assistance to the specific demands aiming at the biopsychosocial maintenance.